2009
DOI: 10.1007/s11164-009-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

UV absorption and fluorescence properties of fused aromatic hydrocarbons having trimethylsilyl, trimethylgermyl, and trimethylstannyl groups

Abstract: Effects of trimethylsilyl, trimethylgermyl, and trimethylstannyl substituents attached to fused aromatic hydrocarbons such as pyrene, anthracene, phenanthrene, and naphthalene were studied in terms of UV absorption and fluorescence properties in aerated cyclohexane solutions. Absorption maxima of trimethylsilyl-, trimethylgermyl-, and trimethylstannyl-substituted aromatic hydrocarbons shifted to longer wavelengths than those of unsubstituted ones. Absorption maxima of mono-, bis-, tris-, and tetrakis(trimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…Close examination of these spectra shows that substituents on silicon of the silyl groups (SiMe 3 , SiMe 2 H, SiMe 2 n Bu, SiMe 2 t Bu, and SiMe 2 n Oct) have only a small effect on the absorption and fluorescence properties of the naphthalene chromophore/fluorophore. In contrast, silyl-substituents at C-9 of anthracene bring about dramatic changes in absorption and fluorescence properties [20,34]. A possible reason for this phenomenon is steric repulsion, which exists between the C-9 silyl groups and peri-hydrogens at C-1 and C-8 of the anthracene ring.…”
Section: Effects Of Hydrogen Atom and Alkyl Group Containing Substitumentioning
confidence: 99%
See 1 more Smart Citation
“…Close examination of these spectra shows that substituents on silicon of the silyl groups (SiMe 3 , SiMe 2 H, SiMe 2 n Bu, SiMe 2 t Bu, and SiMe 2 n Oct) have only a small effect on the absorption and fluorescence properties of the naphthalene chromophore/fluorophore. In contrast, silyl-substituents at C-9 of anthracene bring about dramatic changes in absorption and fluorescence properties [20,34]. A possible reason for this phenomenon is steric repulsion, which exists between the C-9 silyl groups and peri-hydrogens at C-1 and C-8 of the anthracene ring.…”
Section: Effects Of Hydrogen Atom and Alkyl Group Containing Substitumentioning
confidence: 99%
“…In addition, the enhancing effects of silyl groups on the fluorescence intensities of aromatic hydrocarbons, such as anthracenes, naphthacenes, pentacenes, triphenylenes, and pyrenes, has been probed and discussed in detail earlier [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Our previous studies in this area have focused on the effects of silyl, silylethynyl, germyl, and stannyl groups on the absorption and fluorescence spectroscopic properties of pyrene [30][31][32][33][34]. In the photochemistry of silylnaphthalenes, the absorption and fluorescence properties as well as the photoreactions of disilanes [35][36][37][38][39] and oligosilanes [40][41][42] have been subjected to detailed investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In investigations carried out recently, we designed and synthesized a variety of functional fluorescent materials that contain the pyrene fluorophore (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). In these studies, we observed that alkynylpyrenes are highly emissive and, as a result, they can be utilized as fluorescent probes for the detection of amino acids, proteins and DNA (53).…”
Section: Introductionmentioning
confidence: 99%
“…Organic substances have some advantages in applications to photoactive materials because they possess unique luminescence properties that are governed by precise molecular designs [1][2][3][4][5][6]. Previously, we and others observed that linking silyl and silylethynyl groups to fused aromatic substances such as naphthalene [7][8][9], anthracene [7,10,11], pyrene [7,[12][13][14][15][16][17] and perylene [18] often increases fluorescence efficiency. However, the highly emissive character of these molecules is limited to highly dilute solutions because fluorescence intensities generally decrease as the concentrations of solutions increase.…”
Section: Introductionmentioning
confidence: 99%